PENGARUH PERSEPSI KONSUMEN MENGENAI HARGA, LOKASI, DAN KUALITAS PASAR MODERN TERHADAP MINAT BELI KONSUMEN - Diki Rikardo Effendi; Riche Fermayani; Ash Shadiq Egim; Romi Rianto Harahap (Jurnal Ecogen, 2021)
This study aims to look at the analysis of the influence of consumer perceptions of price, location, and modern market quality on consumer buying interest in PT. Ramayana Lestari Sentosa Padang Branch (case study at the Robinson Supermarket Padang Branch). The sample in this study was measured by distributing questionnaires to 100 consumers at the Padang branch of Robinson Supermarket so that there were 100 research samples. Based on the results of the partial t test it can be concluded that prices have a negative and significant effect on consumer buying interest because the significance value is 0.047 < 0.05 which is supported by the value of t count of -2,016 < t table of -1,983. Based on the partial t test it can be concluded that the location has a positive and significant influence on consumer buying interest because the significance value is 0.003 < 0.05 which is supported by the value of t count of 3.037 > t table of 1.983. Based on the partial t test it can be concluded that market quality has a positive and significant influence on consumer buying interest because the significance value is 0,000 <0,05 which is supported by the value of t count of 9,298 > t table of 1,983. Based on the simultaneous F test it can be concluded that the price, location and market quality together or simultaneously have an influence on consumer buying interest because the significance value for the simultaneous F test is 0,000 < 0,05 which is supported by the calculated F value of 68,843 > F table amounting to 2,462. The ability of the independent variable in this case is the price, location and market quality of the dependent variable in this case is the consumer buying interest of 67.3% while the remaining 33.7% is influenced by other variables other than variables not included in the research model such as promotion.Keywords: price, location, market quality, and consumer buying interest